Pendekatan Konstektual Dalam Pembelajaran Pendidikan Agama Islam - Fitriyani, Fitriyani; Puspitasari, Novi; Hairil, Alta (Edification Journal : Pendidikan Agama Islam, 2024)
The purpose of this writing is to know and understand the contextual approach as a teaching method that supports success in the PAI learning process. The method used in this research is a literacy study method where data collection uses various reading sources such as journals, books and articles to support the success of this writing. From the results of this writing, it can be concluded that the definition of a contextual approach is a way of teaching carried out by teachers by linking learning material to students' daily lives in the real world, so that students are able to draw meaning or conclusions from the learning material. The aim of this contextual approach is to build students' understanding of new experiences based on initial knowledge. Learning becomes a process of building knowledge rather than receiving knowledge.